PENGARUH CORPORATE GOVERNANCE, LEVERAGE, PROFITABILITAS, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - YOSEPH ANASTASIUS DIDIK CAHYANTO; EUIS NURISTA MANASARI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this research is to provide empirical evidence about the effect of independent variables, namely institutional ownership, managerial ownership, independent board of commissioners, audit committee, leverage, profitability, sales growth, firm size, and audit quality on the dependent variable, namely earnings management. This research used a population of nonfinancial companies listed on the Indonesia Stock Exchange in 2017-2019. The sample used was 366 sample data, which were selected using a purposive sampling method. The hypothesis in this research used the multiple regression analysis method on SPSS v25. The results of this research indicate that the variable leverage and sales growth have influence on earnings management, while variables institutional ownership, managerial ownership, independent board of commissioners, audit committee, profitability, firm size, and audit quality have no influence on earnings management